Amazonian Ecocentrism as an Emerging Alternative in the Environmental Crisis: Contributions Related to Animal Otherness - Delgado, Ana Dolores Verdú (Journal of Ecohumanism, 2025)
This article explores some aspects of the ecocentric thinking implicit in the ancestral cosmovisions of Amazonian peoples with the intention of shedding light on the relationship between respect for animal otherness and ecosystem balance. The research is based on a review of anthropological texts that focus on the Amazonian cultures of Latin America, and on specific contributions of Latin American feminisms that represent a critique of anthropocentrism. Finally, it analyses the concept of reciprocity applied to the relationship between humans and nature. The essay is a critique of the reification of animals, not only from an ethical point of view, but also because of its impact on the environmental crisis, as it is functional to the economic system that has produced the current environmental and climate crisis.